(untitled) (Asian Journal of Pharmaceutics (AJP), 2020)
Background: This study evaluated the association between warfarin knowledge and patients’ reported outcomes (PROs) among warfarin patients. Methods: A cross-sectional study was performed among warfarin patients in Pakistan. Warfarin knowledge was evaluated using a self-developed and pre-validated instrument. Descriptive and inferential statistics were applied to observe patients’ demographic features and to determine the correlation among different PROs regarding the adverse events among warfarin patients. Spearman’s rank-order correlation matrix was used to determine the association between knowledge mean scores and the PROs of adverse events. Results: Among total 295 patients, females were more than males (n = 184, 62.4% and n = 111, 37.6%, respectively). The mean knowledge score was 6.62 ± 2.68 and the correlation coefficients between the mean knowledge score and the studied PROs were statistically significant. Conclusion: Statistically, a significant positive correlation (P < 0.05) was observed between the mean knowledge score of the participants and the adverse events’ PROs.